De-demonising universality : transcultural dragons and the universal agent in J.K. Rowling's Harry Potter and David Eddings' The Belgariad - Steenkamp, Janka (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (English))--University of Stellenbosch, 2009.